2007
DOI: 10.1007/s00213-007-0834-8
|View full text |Cite
|
Sign up to set email alerts
|

Intracerebroventricular administration of nitric oxide-sensitive guanylyl cyclase inhibitors induces catalepsy in mice

Abstract: This study showed that pharmacological disruption of the endogenous NO-sGC signaling in the central nervous system induces long-lasting catalepsy in mice. Moreover, the cataleptic effect of NOS inhibition correlates with the decrease in NO( x ) products formation in the striatum. The results give further support to the hypothesis that NO plays a role in motor behavior control mediated, at least in part, by cyclic guanosine monophosphate production in the striatum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 53 publications
1
7
0
Order By: Relevance
“…The induction of motor behavior in sGC-KD mice was not detected in the first 5 min of the test (sGCβ1 KD vehicle 714 ± 76 cm; control 621 ± 95 cm; P = 0.12) (Fig. 1I) whereas acute administration of the nitric oxide synthase inhibitor L-NG-nitroarginine methyl ester, (L-NAME) to sGCβ1 KD mice attenuated movement (90 ± 20 cm) as previously shown in WT (8,9), suggesting that extrastriatal NOS are…”
Section: Resultssupporting
confidence: 69%
“…The induction of motor behavior in sGC-KD mice was not detected in the first 5 min of the test (sGCβ1 KD vehicle 714 ± 76 cm; control 621 ± 95 cm; P = 0.12) (Fig. 1I) whereas acute administration of the nitric oxide synthase inhibitor L-NG-nitroarginine methyl ester, (L-NAME) to sGCβ1 KD mice attenuated movement (90 ± 20 cm) as previously shown in WT (8,9), suggesting that extrastriatal NOS are…”
Section: Resultssupporting
confidence: 69%
“…(1991) showed that a high dose of L-NAME (600 mg/kg) had a nearly sedative effect in rats. Moreover, NOS inhibitors N G -nitro-L-arginine (L-NOARG), L-NAME and 7-nitroindazole (7-NI, a relatively selective inhibitor of neuronal NOS) induced catalepsy in mice and rats (Echeverry et al ., 2007; Lazzarini et al ., 2005; Del Bel et al ., 2004). In studies of Volke et al .…”
Section: Involvement Of Nitric Oxide In Animal Behaviourmentioning
confidence: 99%
“…For example, studies by Del Bel et al (2005) have shown that striatal nNOS interneurons play a critical role in the generation of motor behavior. Systemic and intrastriatal exposure to NOS and sGC inhibitors has been shown to depress basal locomotion and induce catalepsy (Stewart et al, 1994; Del Bel et al, 2004; Echeverry et al, 2007). Pharmacological disruption of NO function also potentiates catalepsy induced via D2-class receptor antagonists (Del Bel and Guimaraes, 2000; Cavas and Navarro, 2002).…”
Section: Striatal Pathophysiology In Parkinson's Disease: Involvementmentioning
confidence: 99%